LIBRARIAN - MIKHAIL ELIZAROV; ANDREW BROMFIELD (LONDON PUSHKIN PRESS, 2015)
A collection of books, written by unpopular Soviet-era novelist Gromov, have incredible mystical powers. When Alexei inherits these as part of an uncle's estate, he has no idea of the power they hold and what a group of readers will do to possess them.
Keywords: RUSSIAN NOVEL-ENGLISH TRNSLATION